2016
DOI: 10.1080/17435390.2016.1196251
|View full text |Cite
|
Sign up to set email alerts
|

Multilaboratory evaluation of 15 bioassays for (eco)toxicity screening and hazard ranking of engineered nanomaterials: FP7 project NANOVALID

Abstract: Within EU FP7 project NANOVALID, the (eco)toxicity of 7 well-characterized engineered nanomaterials (NMs) was evaluated by 15 bioassays in 4 laboratories. The highest tested nominal concentration of NMs was 100 mg/l. The panel of the bioassays yielded the following toxicity order: Ag > ZnO > CuO > TiO2 > MWCNTs > SiO2 > Au. Ag, ZnO and CuO proved very toxic in the majority of assays, assumingly due to dissolution. The latter was supported by the parallel analysis of the toxicity of respective soluble metal sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 63 publications
4
48
1
Order By: Relevance
“…In literature, adult zebrafish have been shown to be highly sensitive to copper (48 h LC 50 of 0.25 mg Cu/L for CuSO 4 $5H 2 O and 48 h LC 50 of 1.56 mg nanocopper/L (Griffitt et al, 2007)). High copper toxicity in standard medium has also been reported for zebrafish embryos (OECD236) in a NP toxicity screening study within the NanoValid project: 96 h EC 50 of 1.6 mg Cu/L (95% CI 0.84e2.24 mg Cu/L) for CuO NNV-011 (Bondarenko et al, 2016). Hua et al (2014) also found Cu NPs highly toxic to zebrafish embryos with 120 h LC 50 for 25 nm Cu NPs 1.03 mg Cu NP/L (95% CI 0.85e1.25) and for Cu(NO 3 ) 2 0.70 mg Cu/L (95% CI 0.68e0.72).…”
Section: Toxicity To Zebrafish Embryo E Cumentioning
confidence: 89%
See 2 more Smart Citations
“…In literature, adult zebrafish have been shown to be highly sensitive to copper (48 h LC 50 of 0.25 mg Cu/L for CuSO 4 $5H 2 O and 48 h LC 50 of 1.56 mg nanocopper/L (Griffitt et al, 2007)). High copper toxicity in standard medium has also been reported for zebrafish embryos (OECD236) in a NP toxicity screening study within the NanoValid project: 96 h EC 50 of 1.6 mg Cu/L (95% CI 0.84e2.24 mg Cu/L) for CuO NNV-011 (Bondarenko et al, 2016). Hua et al (2014) also found Cu NPs highly toxic to zebrafish embryos with 120 h LC 50 for 25 nm Cu NPs 1.03 mg Cu NP/L (95% CI 0.85e1.25) and for Cu(NO 3 ) 2 0.70 mg Cu/L (95% CI 0.68e0.72).…”
Section: Toxicity To Zebrafish Embryo E Cumentioning
confidence: 89%
“…CuO nanoparticles (CuO NNV-011, provider Intrinsiq Materials, nanoscaled powder with primary particle size of 22e25 nm) were in powder form. The initial (above-mentioned) NP characterization data are from the providers but the same type of Ag NPs have been previously characterized and described in Bondarenko et al, 2016;B€ ohme et al, 2015, Zou et al, 2015and CuO NPs in Bondarenko et al, 2016 (see SI, Table S1). As ionic controls, analytical grade metal salts AgNO 3 and CuSO 4 $5H 2 O were used.…”
Section: Nanoparticles and Sample Preparationmentioning
confidence: 97%
See 1 more Smart Citation
“…TiO 2 nanoparticles were also used as antibacterial agents and colorants in paints and food packaging [14,15], which were likely to then migrate into the environment or food sources and cause potential harm to organisms. In addition, nanoparticles in food can penetrate into the digestive tract lymphatic vessels, and compared with other large particles, can be more easily distributed into other tissues and organs [16].Organisms of different trophic levels are usually selected to assess the ecotoxicity of NPs, including primary producers (algae), consumers (mammals, crustaceans) and decomposers (microbes) [17]. Among them, algae are the most widely used to evaluate the ecotoxicity of NPs.…”
mentioning
confidence: 99%
“…Organisms of different trophic levels are usually selected to assess the ecotoxicity of NPs, including primary producers (algae), consumers (mammals, crustaceans) and decomposers (microbes) [17]. Among them, algae are the most widely used to evaluate the ecotoxicity of NPs.…”
mentioning
confidence: 99%